Residential satisfaction with management services at Taman Tasik Mewah condominium, Seremban, Malaysia - Zainal Abidin, Izu Adilla (2012)

(untitled)
The efficiency of management company performance of condominium housing is being determined by resident‟s satisfaction level on the performance of services provided by management. This research study seeks to analyse and identify factors influencing residential satisfaction upon services and facilities provided. The study was stationed at Condominium Taman Tasik Mewah, Seremban, Negeri Sembilan targeting 208 respondents whom are chosen residents of the condominium through simple random sampling. Period of study was between March and April of year 2010.